Analisis Perilaku Penelusuran Informasi Pemustaka Dalam Upaya Pemenuhan Kebutuhan Informasi di Perpustakaan UINSU - Aina Sabriyanti; Franindya Purwaningtyas; Franindya Purwaningtya; Restiana Restiana; Putri Lestari; Adha Rahimi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to determine the behavior in searching for user information in meeting the information needs of the UINSU Tuntungan library, to determine the behavior pattern in searching for user information in meeting information needs at the UINSU Tuntungan library, to find out the obstacles that occur in searching for user information in an effort to fulfill information needs of the UINSU Tuntungan library. This research uses the type of qualitative research that requires as much information and data as possible to achieve the research objectives. This type of research is a case study because this research is carried out in depth on an institution and with a narrow subject. As a case study, the data collected came from various library sources. This study resulted that in order to determine the behavior of the user before searching for information, the researcher conducted interviews with several informants who were considered to be able to provide information to the researcher. There are several stages that can be used by users in finding information in the library. In conducting information search there are 6 stages developed by Kuhlthau, namely initiation, selection, exploration, formulation, collection and presentation. Keywords: Information Search, User, Information Needs